Leadership in Managing BMX Organizations - Fannisya Dania S Pane (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
The success, enthusiasm, and longevity of community-based sports organizations like BMX are determined by leadership, which is a key component. Using a systematic literature review technique, this study seeks to examine the function of leadership in directing BMX groups. The evaluation procedure included the identification and analysis of trustworthy international scientific publications released between 2021 and 2025 using keywords related to sports leadership and organizational leadership in the Scopus, ScienceDirect, Taylor & Francis Online, and Google Scholar databases. The synthesis findings show that transformational, situational, and participatory leadership styles are the most successful strategies for boosting member participation, improving organizational culture, and encouraging creativity in BMX communities. These leadership approaches help to foster a supportive atmosphere, improve team cohesion, and make it easier to adjust to technological and social developments that have an impact on extreme sports. As it incorporates flexibility, teamwork, and a developmental approach to members, this research concludes that adaptive leadership is the most pertinent leadership style for BMX groups. The results offer theoretical contributions to the literature on sports leadership and practical implications for community leaders in improving the management effectiveness of BMX groups.